PETROLEUM HYDROCARBONS POLLUTION OF NIGERIAN WATERS AND SEDIMENTS AROUND LAGOS AND NIGER DELTA AREA OF NIGERIA (1989)
There is a paucity of scientific data on the levels and pattern of distribution of petroleum hydrocarbons in the Nigerian aquatic environment. The levels of total hydrocarbons in 241 water and 222 sediment samples in’ the major river systems draining into Nigerian coastal environment around Lagos and the Niger Delta area have been used to monitor the pattern of distribution of hydrocarbons within these areas over different weather regimes during 1984-85. The Utorogu pipeline oil spillage incident in Bendel State of Nigeria in 1984 was used as a case study for assessment of environmental impact of oil spillage in aquatic ecosystem in Nigeria. Samples were also collected and analyzed for total hydrocarbons from Kaduna (Northern Nigeria) and Ibadan (Western Nigeria) for comparative information and controls respectively. Water samples were analyzed for petroleum hydrocarbon by infrared (IR) and gas chromatographic (GC) techniques whereas sediment samples were analyzed by gravimetry and gas chromatography (GC). The infrared (IR) results for 1984 (wet season) showed that Lagos and Lekki lagoons had hydrocarbon level (presented as range followed by mean value in bracket), 1.64-11.40 (5.60) mg/1; Niger Delta, ND (net detectable)-70.70 (6.18)mg/1; Utorogu 0.17-10.50 (2.22)mg/1; Kaduna 4.30-9.90 (6.98)mg/1, while Ibadan water samples (serving as control area) showed no detectable levels of hydrocarbon. In 1985 (dry season) there was a decrease in the hydrocarbon levels found in the water samples. Lagos and Lekki lagoons recorded 0.10-0.41 (0.25)mg/1; Niger Delta 0.10-1.80(0.52)mg/1 and Utorogu 0.17-4.67 (2.14)mg/1. The gas chromatographic values for hydrocarbon concentration in water were much lower than the infrared values. All the samples except Upomani discharge point (3.36 mg/1) had values below 1 mg/1 by GC. Nonetheless, the IR values correlated well with the GC values. The corresponding hydrocarbon levels (on dry weight basis) in sediment samples in 1984 were: Lagos and Lekki lagoons ND-95.54 (30.33) µg/g; Niger Delta ND-74.05 (9.09) µg/g; Utorogu 14.04- 267.48 (98.88) µg/g and Kaduna 0.62-21.52 (12.36) µg/g. In 1985 the values of hydrocarbon levels recorded in the sediment samples were as follows: Lagos and Lekki lagoons 0.20-10.30 (4.20) µg/g; Niger Delta 0.05-44.06 (6.64) µg/g; Utorogu (Jan-Feb.) ND-9.41 (2.98) µg/g; Utorogu (June-July) 0.03- 68.06 (21.66) µg/g; Kaduna 2.91-5.00 (3.96) µg/g and Ibadan 8.09-27.79 (17.94) µg/g. The Lagos lagoon sediment samples monitored from January to December 1985 gave ND-2766.27 (11.13) µg/g. The results of this work showed that Lagos lagoon was more polluted than the Niger Delta in terms of petroleum hydrocarbons. Highest values of petroleum hydrocarbons were recorded close to oil activity points such as Ogharife field effluent canal, Chanomi creek at Egwa field, Orughene creek, in the Niger Delta area; or near human settlements such as Obotebe and Bakana or in an industrial area like Lever Brother's discharge point and Berger/National Oil/Ijora in Lagos. The results of Utorogu oil spillage gave a picture of the impact of oil in the aquatic environment. During the first sampling trip which took place within four months after the oil incident, aquatic lives (plants and animals) were seriously affected in the Utorogu swamp, but before the end of the study period (June 1985) the swamp had recovered and was bubbling with life again. Oil pollution indicator parameters such as the Carbon Preference Index (CPI), Pristane: Phytane ratio (Pr/Ph); Presence of Phytane, and Unresolved Complex Mixture (UCM) and the Marine Oil Pollution Index (MOPI) indicated that some of the stations were polluted by oil while most of the points studied in both Lagos and the Niger Delta were contaminated with petroleum hydrocarbons which may be from crude oil, refined oil or both. Moreover, all the contaminated and polluted samples showed petroleum hydrocarbon at different stages of weathering as reflected in their carbon range, the Pristane: n-C(17); Phytane:n-C(18) and UCM: n-alkane ratios.